On-Reading (Chinese-Style Pronunciation) Predominance Over Kun-Reading (Native Japanese Pronunciation) in Japanese Semantic Dementia - Sakurai, Yasuhisa; Uchiyama, Yumiko; Takeda, Akitoshi; Terao, Yasuo (Frontiers in Human Neuroscience, 2021)
Japanese kanji (morphograms) have two ways of reading: on-reading (Chinese-style pronunciation) and kun-reading (native Japanese pronunciation). It is known that some Japanese patients with semantic dementia read kanji with on-reading but not with kun-reading. To characterize further reading impairments of patients with semantic dementia, we analyzed data from a total of 9 patients who underwent reading and writing tests of kanji and kana (Japanese phonetic writing) and on-kun reading tests containing two-character kanji words with on-on reading, kun-kun reading, and specific (so-called Jukujikun or irregular kun) reading. The results showed that on-reading preceding (pronouncing first with on-reading) and kun-reading deletion (inability to recall kun-reading) were observed in nearly all patients. In the on-kun reading test, on-reading (57.6% correct), kun-reading (46.6% correct), and specific-reading (30.0% correct) were more preserved in this decreasing order (phonology-to-semantics gradient), although on-reading and kun-reading did not significantly differ in performance, according to a more rigorous analysis after adjusting for word frequency (and familiarity). Furthermore, on-substitution (changing to on-reading) errors in kun-reading words (27.0%) were more frequent than kun-substitution (changing to kun-reading) errors in on-reading words (4.0%). These results suggest that kun-reading is more predominantly disturbed than on-reading, probably because kun-reading and specific-reading are closely associated with the meaning of words.